Impact of Sustainability Balanced Scorecard Types on Environmental Investment Decision-Making - Jassem, Suaad; Che Azmi, A.A.; Zakaria, Zarina (MDPI, 2018)
Investment decision-making based on aspects of sustainability is gaining importance among organizations around the globe. In this context, there is a need for quality investment decisions, which require sufficient knowledge among organizational managers about managing sustainability information to achieve environmental objectives that meet stakeholder expectations. This has led to the emergence of organizational performance measuring tools such as the Sustainability Balanced Scorecard, which integrates the environmental perspective into the traditional Balanced Scorecard. Using experimental research method, the objective of this study is to investigate the indirect effect of Eco-efficiency knowledge and Sustainability Balanced Scorecard knowledge as mediators influencing the relationship between Sustainability Balanced Scorecard types and their impact on environmental investment decision-making. Findings of the current research are based on 60 respondents who were randomly assigned to one of the following two types of Sustainability Balanced Scorecard architecture: (1) environmental data embedded within the traditional Balanced Scorecard perspectives; and (2) standalone environmental data as an additional fifth perspective along with the traditional Balanced Scorecard architecture. The traditional Balanced Scorecard without any information on environmental perspective is included in the experiment as the control condition. The findings indicate that the combined effect of ecoefficiency knowledge and Sustainability Balanced Scorecard knowledge has a significant positive influence on the relationship between the Balanced Scorecard type versus Sustainability Balanced Scorecard type and environmental investment decision-making.